Pengaruh Kecerdasan Emosional Terhadap Akhlak Siswa Kelas VIII di SMP Negeri 1 Parittiga Bangka Barat - Devita, Devita; Rahman, Priyanggo Karunia (Fakultas Tarbiyah, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2023)
A more tangible direct effect on one's behavior will be derived from any experience involving extreme emotions. Therefore, emotional intelligence is necessary for one to be able to control his emotions and direct them in a more positive direction. The objective of this study is to find out whether emotional intelligence affects the morals of students in the State High School 1 Parittiga Western Frame and how much the influence of emotional intelligence is on student morals. Quantitative and correlational methods are used in this research. The study consisted of 87 students. A simple random sample method, using the Slovin formula, was used to count the sample of 71 students. The research consists of lifting, interviews, and regression analysis documented with simple linear regression. As the results of the study show, there is a significant correlation between the emotional intelligence of students at 1st State Parittiga High School and their morals. The results of a simple regression test show this. A t count of 5,524 and a Sig value of 0.000 are obtained. With free degrees df = 71-2 = 69, the ttable value is 1,667. Therefore, it can be concluded that thitung is larger than ttable (5,524 is larger than 1,667), and the Sig value is less than 0.05 (0,000 kurang dari 0,05). Eighth grade students at State 1 Parittiga High School, West Bank, see the influence between emotional intelligence (X) and morality (Y). The result indicates that Ha is accepted and HO is automatically rejected. Furthermore, with the R Square value of 30.7%, we can find that the influence of the free variable on the bound variable is 30.7%. Other components that are not considered variables affect the remaining 69.3%.